SISTEM INFORMASI AKUNTANSI BERBASIS MAJA LABO DAHU DALAM UPAYA MENCEGAH TERJADINYA FRAUD - Marhamatussanyyah, Marhamatussanyyah; Bulutoding, Lince; Aditiya, Roby (ISAFIR: Islamic Accounting and Finance Review, 2023)
This study aims to determine how important it is to implement an accounting information system that is supported by the maja labo dahu concept in a company to prevent fraud. This research was conducted at the Regional Asset Financial Management Agency (BPKAD) office in the city of Bima. The object of research taken by the researcher is an accountant employee who works at the BPKAD office in the city of Bima. This type of research is a qualitative research using a Phenomenological research approach. The type of data used in this study is subject data in the form of information obtained from interviews with respondents. The results of this study indicate that the application of an accounting information system in the planning and implementation process has been said to be effective, by balancing the values ​​of the maja labo dahu (shame and fear) concept which contains the value to always be ashamed and afraid of violating the laws of norms and religion so that by The value of this philosophy can be said to be able to prevent someone from committing fraud.